Application of Polygonum minus extract in enhancing drought tolerance in maize by regulating osmotic and antioxidant system - Kasim, Susilawati; Deng, Xi; Yang, Zhongming; Saidi, Noor Baity; Uddin, Md Kamal; Han, Mingzhao; Mohd Shuib, Effyanti (Tech Science Press, 2024)
Drought stress is a major factor affecting plant growth and crop yield production. Plant extracts as natural biostimulants hold great potential to strengthen plants to overcome drought impacts. To explore the effect of Polygonum minus extract (PME) in enhancing drought tolerance in plants, a study was set up in a glasshouse environment using 10 different treatment combinations. PME foliar application were designed in CRD and effects were closely observed related to the growth, physiology, and antioxidant system changes in maize (Zea mays L.) under well-watered and drought conditions. The seaweed extract (SWE) was used as a comparison. Plants subjected to drought stress exhibited a significant reduction in fresh weight, dry weight, relative water content (RWC), and soluble sugar, but they stimulated the phenolic, flavonoid, proline, glutathione (GSH), malondialdehyde (MDA) and antioxidant enzyme (catalase, CAT; peroxidase, POD; superoxide dismutase, SOD) activities. Foliar application of PME improved fresh and dry weight (FW: 33.1%~41.4%; DW: 48.0%~43.1%), chlorophyll content (Chl b: 87.9%~100.76%), soluble sugar (23.6%~49.3%), and soluble protein (48.6%~56.9%) as well as antioxidant enzyme activities (CAT and POD) compared to CK under drought conditions. while decreasing the level of MDA. Notably, the mitigating effect of PME application with high concentration was more effective than those of SWE. Our study reveals that PME could alleviate drought stress by regulating osmoprotectant content and antioxidant defense system and can be used as an economical and environmentally friendly biostimulants for promoting maize growth under drought stress.